Performance measurement of the petroleum industry : functional profitability and alternatives - Beckenstein, Alan R.; Beckenstein, Alan R.; Grayson, Leslie E.; Overholt, Susan H.; Sutherland, Timothy F. (Lexington, Mass. : Lexington Books, 1979)
This book reviews the evidence of the separate traditions of performance measurement in the petroleum industry. Since policy analysis was a forefront concern, the contents of the book focus on defining useful answers to policy questions.
Includes index.
kjo 14/01/2019
Loans
Keywords: Petroleum industry and trade; Industrial efficiency